2020
DOI: 10.1093/icb/icaa094
|View full text |Cite
|
Sign up to set email alerts
|

Larval Dispersal Modeling Suggests Limited Ecological Connectivity Between Fjords on the West Antarctic Peninsula

Abstract: Abstract Larval dispersal is a key process for community assembly and population maintenance in the marine environment, yet it is extremely difficult to measure at ecologically relevant spatio-temporal scales. We used a high-resolution hydrodynamic model and particle-tracking model to explore the dispersal of simulated larvae in a hydrographically complex region of fjords on the West Antarctic Peninsula. Modeled larvae represented two end members of dispersal pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 129 publications
0
3
0
Order By: Relevance
“…Modeling by Hahn-Woernle et al ( 2020) found a significant exchange of surface waters between Andvord Bay and the Gerlache Strait, which causes the fjord to lose or gain heat, mainly driven by winds. In addition, both planktonic organisms (larvae), chlorophyll a, and macro-and micronutrients originating within the fjords can be exported to the Gerlache Strait within a month, an exchange strongly enhanced by recurrent katabatic winds (Ekern, 2017;Ziegler et al, 2020;Forsch et al, 2021). Similar processes have been reported for Arthur Harbor in Anvers Island and Southeast Greenland, suggesting wind-driven exchange of surface waters is a common process in high-latitude nearshore areas (Moline and Prezelin, 1996;Spall et al, 2017).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Modeling by Hahn-Woernle et al ( 2020) found a significant exchange of surface waters between Andvord Bay and the Gerlache Strait, which causes the fjord to lose or gain heat, mainly driven by winds. In addition, both planktonic organisms (larvae), chlorophyll a, and macro-and micronutrients originating within the fjords can be exported to the Gerlache Strait within a month, an exchange strongly enhanced by recurrent katabatic winds (Ekern, 2017;Ziegler et al, 2020;Forsch et al, 2021). Similar processes have been reported for Arthur Harbor in Anvers Island and Southeast Greenland, suggesting wind-driven exchange of surface waters is a common process in high-latitude nearshore areas (Moline and Prezelin, 1996;Spall et al, 2017).…”
Section: Discussionmentioning
confidence: 65%
“…The waters of the Gerlache Strait are characterized by long residence times that can range from weeks to months and it is estimated that within coastal areas this residence time may be longer (Zhou et al, 2002), which may explain this interconnectedness between coastal areas and the long persistence of phytoplankton assemblages. Studies from Andvord Bay can explain the interconnectedness between the Strait and the coastal areas affecting inshore phytoplankton assemblages (Ekern, 2017;Lundesgaard et al, 2019;Hahn-Woernle et al, 2020;Lundesgaard et al, 2020;Ziegler et al, 2020;Forsch et al, 2021). Modeling by Hahn-Woernle et al ( 2020) found a significant exchange of surface waters between Andvord Bay and the Gerlache Strait, which causes the fjord to lose or gain heat, mainly driven by winds.…”
Section: Discussionmentioning
confidence: 99%
“…A major challenge is to document ecosystem responses at all levels of biological organization (genome to pan‐Antarctic), and combine genomics/DNA approaches with multi‐taxon studies that integrate taxonomic, biogeochemical, genomic, and community data followed by matching biological data with fluxes/transports measured by physical oceanographers, geochemists, and geologists (e.g., Halanych & Mahon, 2018). We also need a better understanding of the mechanistic linkages between climate, sea ice and ice shelves, ice sheets and icebergs, biogeochemical processes, food webs and organism interactions, and population and community dynamics (e.g., Lundesgaard et al, 2020; Ziegler, Cape, et al, 2020; Ziegler, Hahn‐Woernle, et al, 2020). Linkages with glaciology, physical oceanography, biology, and ecological interactions are critical as both drivers and impacts of ice‐shelf loss (Ducklow, 2008; Ducklow et al, 2007; Massom & Stammerjohn, 2010).…”
Section: Overcoming Major Knowledge Gapsmentioning
confidence: 99%